Development of a process chain for digital design and manufacture of patient-specific intervertebral disc implants with matching endplate geometries - De Beer, Neal (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Industrial Engineering))--University of Stellenbosch, 2011.